Impacts of adiposity parameters on peak expiratory flow rate in healthy young adults of Bahria University Medical and Dental College Karachi: cross-sectional study - Ali, Rabiya; Shaikh, Saifullah; Siddiqui, Navaid; Fahad, Muhammad; Shireen Jawed; Masood, Naila (Journal of the Pakistan Medical Association, 2022)
Objectives: To explore the association of various adiposity parametersin young adults. Method: The cross-sectional study was conducted at Bahria University Medical and Dental College, Karachi, from January to February 2021, and comprised healthy medical students aged 19-21years. Height, weight, body mass index, waist circumference, waist-hip ratio and percentage body fat were recorded. Peak expiratory flow rate was determined using Wright’s meter, and its association with adiposity markers was determined using regression analysis. Data was analysed using SPSS 22. Results: Of the 162 subjects, 96(59.3%) were females and 66(40.7%) were males. The overall mean age was 20.18±1.01 years. Peak expiratory flow rate was significant positively associated with height, body mass index, waist circumference, and percentage body fat (p<0.05). It had weak negative association with waist-hip ratio(p>0.05). Conclusion: Peak expiratory flow rate increased with height, body mass index, waist circumference, and percentage body fat in healthy subjects. Key Words: Peak expiratory flow rate, Waist-hip ratio, Body mass index, Visceral fat percentages, Young healthy adults.